(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Ihara Saikaku was poet and novelist, one of the most brilliant figures of the 17th-century revival of Japanese literature. Saikaku in his works such as "The Eternal Storehouse of Japan" and "This Scheming World" described the life of townspeople, merchants, artisans, peasants. He reflects on how to live and work in order to get rich, and about new ways of trade and handicrafts that bring income, the detailed coverage of the feelings and thoughts of the townspeople determines the relevance of the article. The main objective of this article is to get an idea of how in the novels of Ihara Saikaku, who is a representative of the 17th century literature, the image of a city dweller is displayed, about those aspects of the way of life of the townspeople that were not covered before that time.